2019
DOI: 10.3389/fonc.2019.01180
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable Response of Metastatic Gallbladder Carcinoma to Apatinib After Failed Multiline Chemotherapies: A Case Report and Literature Review

Abstract: Gallbladder carcinoma (GBC) is a relatively rare and aggressive malignant tumor with a poor prognosis. A systematic review of current clinical studies illustrates an extreme paucity of second-line therapeutic options following the failure of standard-of-care cisplatin-gemcitabine chemotherapy. The efficacy of apatinib, an highly potent and selective oral inhibitor of VEGFR-2 tyrosine kinase, for refractory advanced GBC has not yet been clarified. Herein, we report a case of advanced GBC that presented a durabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…For molecular targeted therapy as second-line therapy, only ivosidenib (a small-molecule targeted inhibitor of IDH1) significantly improved median PFS compared with placebo (2.7 months vs 1.4 months, hazard ratio 0.37, one-sided p<0.0001) in patients with previously treated IDH1-mutant cholangiocarcinoma [21]. Notably, various retrospective analyses and clinical case reports suggest apatinib has promising activity and manageable toxicity for the pretreated patients with advanced biliary tract cancers, with ORR around 15% and median PFS around 3.0 months [19,[22][23][24]. In this study, apatinib monotherapy preliminarily showed an underlying anti-tumor activity in patients with advanced CCA, which confirmed the potential therapeutic value of anti-angiogenesis strategy and encouraged further exploration of anti-angiogenesis drugs in chemotherapy refractory CCA.…”
Section: Discussionmentioning
confidence: 99%
“…For molecular targeted therapy as second-line therapy, only ivosidenib (a small-molecule targeted inhibitor of IDH1) significantly improved median PFS compared with placebo (2.7 months vs 1.4 months, hazard ratio 0.37, one-sided p<0.0001) in patients with previously treated IDH1-mutant cholangiocarcinoma [21]. Notably, various retrospective analyses and clinical case reports suggest apatinib has promising activity and manageable toxicity for the pretreated patients with advanced biliary tract cancers, with ORR around 15% and median PFS around 3.0 months [19,[22][23][24]. In this study, apatinib monotherapy preliminarily showed an underlying anti-tumor activity in patients with advanced CCA, which confirmed the potential therapeutic value of anti-angiogenesis strategy and encouraged further exploration of anti-angiogenesis drugs in chemotherapy refractory CCA.…”
Section: Discussionmentioning
confidence: 99%